2020
DOI: 10.1371/journal.ppat.1008442
|View full text |Cite
|
Sign up to set email alerts
|

Latency reversal agents modulate HIV antigen processing and presentation to CD8 T cells

Abstract: Latency reversal agents (LRA) variably induce HIV re-expression in CD4 T cells but reservoirs are not cleared. Whether HIV epitope presentation is similar between latency reversal and initial infection of CD4 T cells is unknown yet crucial to define immune responses able to detect HIV-infected CD4 T cells after latency reversal. HIV peptides displayed by MHC comes from the intracellular degradation of proteins by proteasomes and post-proteasomal peptidases but the impact of LRAs on antigen processing is not kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…Disappointingly, none of these studies resulted in a significant decrease in the size of the HIV reservoir in individuals on ART. Several factors may explain these negative results: (a) LRAs may have differential effects between tissues (177); (b) LRAs are not equally efficient in all populations of CD4 + T cells, suggesting that they may be largely ineffective in some cellular reservoirs (107,108); (c) effector cells may be lacking at sites of active viral production such as lymph nodes (14,15,17); (d) the persistent immune exhaustion of CD8 + T cells may not allow the efficient elimination of productively infected cells (182); (e) some LRAs, particularly HDACis, have been shown to impair cytotoxic effector responses (183) and antigen presentation by APCs (184), which could hamper viral reservoir elimination; and (f) productively infected cells may be inherently resistant to immunemediated killing through the expression of prosurvival factors (185).…”
Section: Targeting Hiv Latency In Vivomentioning
confidence: 99%
“…Disappointingly, none of these studies resulted in a significant decrease in the size of the HIV reservoir in individuals on ART. Several factors may explain these negative results: (a) LRAs may have differential effects between tissues (177); (b) LRAs are not equally efficient in all populations of CD4 + T cells, suggesting that they may be largely ineffective in some cellular reservoirs (107,108); (c) effector cells may be lacking at sites of active viral production such as lymph nodes (14,15,17); (d) the persistent immune exhaustion of CD8 + T cells may not allow the efficient elimination of productively infected cells (182); (e) some LRAs, particularly HDACis, have been shown to impair cytotoxic effector responses (183) and antigen presentation by APCs (184), which could hamper viral reservoir elimination; and (f) productively infected cells may be inherently resistant to immunemediated killing through the expression of prosurvival factors (185).…”
Section: Targeting Hiv Latency In Vivomentioning
confidence: 99%
“…Furthermore, the molecular mechanism by which NTP modulates the antigen presentation pathway is not known. Other more robust latency reversal agents have been reported to alter antigen processing by affecting the breadth and production of HIV-1 peptides presented on MHC I [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that late Panobinostat but not early Panobinostat led to a significant loss in DNA methylation at a loci in the gene Fragile Histidine Triad Diadenosine Triphosphtatase (FHIT). Recent work has shown that FHIT gene transfection in mice restores MHC-I expression, and Panobinostat has been shown to augment the expression of MHC genes and HIV antigen processing and presentation [57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%